PENGARUH MASSA KATALIS DAN WAKTU REAKSI PADA PEMBUATAN BIODIESEL DARI LIMBAH MINYAK JELANTAH DENGAN MENGGUNAKAN KATALIS HETEROGEN K2O DARI LIMBAH KULIT KAKAO - Jefry R Turnip, Trio F. L. Tarigan, Mersi Suriani Sinaga (Universitas Sumatera Utara, 2017)
Waste cooking oil is a waste oil that comes from many types of cooking oils such as corn oil, vegetable oil, ect. The purpose of this research is to waste cooking oil as a raw material to form biodiesel with K2O as the solid catalyst from cocoa pod ash (CPA) which is calcined on temperature 650 oC within 4 hours. This oil contains a high level of Free Fatty Acid (FFA) that is 3.13%. Therefore, pretreatment should be done by using activated carbon (1% w/w) to reduce levels of FFA. The research will be observed the effect of reaction time and the mass of catalyst. The characteristics of biodiesel is analyzed according to the levels of methyl ester in biodiesel, density, and viscosity based on the Indonesian National Standard (SNI). The best conditions of biodiesel are obtained with the amount of catalyst is 6% (w/w) that is calcined at 650 °C, reaction time 180 minutes, ratio mol of alcohol : oil is 12: 1, and 65 oC reaction of temperature, resulting the purity and yield of biodiesel is 99,8% and 92,68%. The results of this research indicates that the use of waste cooking as a raw material is suitable in the manufacture of biodiesel.